Colona rivularis (Malvaceae) a new species from Thailand - Suddee, Somran; Rueangruea, Sukid; Poopath, Manop; Karaket, Preecha; Kiewbang, Wittawat; Middleton, David (Thai Forest Bulletin (Botany), 2020)
Colona rivularis, a new species from North-Eastern and Eastern Thailand is described and illustrated.